The Lilliputians of environmental regulation : the perspective of state regulators - Pautz, Michelle C. (Routledge research in environmental policy and politics ;, 2013)
"When we think about environmental policy and regulation in the U.S., our attention invariably falls on the federal level and, more specifically, the U.S. Environmental Protection Agency. Although such a focus is understandable, it neglects the actors most responsible for the implementation and maintenance of the nation's environmental laws - the states. Recognition of the importance of the states still ignores an even smaller subsection of actors, inspectors. These front-line actors in state environmental agencies are the individuals responsible for writing environmental rules and ensuring compliance with those rules. They play an important role in the environmental regulatory state.With data collected from more than 1,300 inspectors across 20 states, Michelle C. Pautz and Sara R. Rinfret take a closer look at these neglected actors to better understand how environmental regulators perceive the regulated community and how they characterize their interactions with them. In doing so, they explore the role these front-line actors play, what it is like to be them, what they think of their place in the environmental regulatory system, and how they interact with the regulated community.An original, timely and unmatched volume advancing the debate on the future of environmental regulation in the U.S"--